1977
DOI: 10.1207/s15327752jpa4103_8
|View full text |Cite
|
Sign up to set email alerts
|

Personality Characteristics Related to Cross-Situational Consistency of Interpersonal Distance

Abstract: Explored the relation of personality dimensions to cross-situational consistency in interpersonal distance. Sixty-five male and 52 female undergraduates were given the Personality Research Form A and the Maudsley Personality Inventory as well as four forms of a measure of interpersonal distance preference which covered 10 different situations. The relationship between the personality dimensions and the consistency of interpersonal distance choice was measured by multiple regression. Neuroticism emerged as havi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1980
1980
2020
2020

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…Long, Calhoun, and Selby (1976) investigated the relations between neuroticism and psychoticism and consistency in selection of interpersonal distance based on multiple-regression analysis. They found that “Neuroticism was the strongest predictor of consistency, being negatively related to interpersonal distance setting across situations” (Harper, et al , 1978, p. 266).…”
Section: Attachment and Proxemicsmentioning
confidence: 99%
“…Long, Calhoun, and Selby (1976) investigated the relations between neuroticism and psychoticism and consistency in selection of interpersonal distance based on multiple-regression analysis. They found that “Neuroticism was the strongest predictor of consistency, being negatively related to interpersonal distance setting across situations” (Harper, et al , 1978, p. 266).…”
Section: Attachment and Proxemicsmentioning
confidence: 99%
“…Long (1984) measured self-reported anxiety and preferred IPD (using a stop-distance technique where the subject indicated the distance at which they would prefer an approaching person to stop) and found that the level of situational setting anxiety was a better predictor of IPD than the self-reported anxiety level. Long, Calhoun and Selby (1977) also used high and low anxiety settings to examine the consistency of personality characteristic influences on seating distance preferences at tables. They found that neuroticism consistently predicted a preference for higher IPDs across the settings.…”
Section: Introductionmentioning
confidence: 99%